2016
DOI: 10.1136/jech-2015-205855
|View full text |Cite
|
Sign up to set email alerts
|

Formative evaluation of a participatory women's group intervention to improve reproductive and women's health outcomes in rural Bangladesh: a controlled before and after study

Abstract: Background Women's groups using participatory methods reduced newborn mortality in rural areas of low income countries. Our study assessed a participatory women's group intervention that focused on women's health, nutrition and family planning. Methods The study was conducted in three districts in Bangladesh between October 2011 and March 2013, covering a population of around 230 000. On the basis of allocation for the preceding cluster randomised trials, three unions per district were randomly allocated to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 19 publications
1
30
1
2
Order By: Relevance
“…Although PLA alone has been effective in reducing neonatal mortality [ 27 ], and in changing nutrition-related behaviours [ 25 , 30 , 31 , 42 ], effects of PLA alone on birthweight were not large enough to reach significance in our study. This is consistent with the lack of effect of PLA plus home visits on birthweight found by Nair et al [ 25 ].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Although PLA alone has been effective in reducing neonatal mortality [ 27 ], and in changing nutrition-related behaviours [ 25 , 30 , 31 , 42 ], effects of PLA alone on birthweight were not large enough to reach significance in our study. This is consistent with the lack of effect of PLA plus home visits on birthweight found by Nair et al [ 25 ].…”
Section: Discussioncontrasting
confidence: 64%
“…However we found that nutrition education interventions using participatory community-based approaches focused on practical behaviour were more likely to be effective than knowledge transfer alone [ 26 ]. Moreover, PLA with women’s groups was effective in reducing other health outcomes, including neonatal and maternal mortality in rural communities [ 27 ], and was pro-poor in coverage [ 28 ] and impact [ 29 ], and may influence nutrition-related behaviours [ 30 ] and dietary diversity [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participatory interventions with women’s groups using a Participatory Learning and Action (PLA) approach have shown large positive impacts on essential newborn care practices and have reduced neonatal deaths [ 38 ]. These interventions have also shown large effects on women’s nutritional knowledge and dietary diversity [ 39 , 40 ], but limited impacts on maternal and child nutritional status [ 40 ]. In PLA groups, women acquire new nutrition knowledge, receive social support from peers and the community, and exercise both problem-solving and decision-making power [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Community-level exposure (to a lesser degree) and individual attendance (to a greater degree) at the groups appears to result in changes in home birth practices and careseeking behaviour for maternal health,5 7 10 leading to reductions in maternal infection rates and more timely intervention as required at delivery 5 7. Women attending the groups, at least in the short term, perceive them to have resulted in increased self-confidence and self-esteem, greater social support12 13 and increased participation in household decision-making, particularly around healthcare (although other studies have not shown impact on household decision making) 14 15. Qualitative data suggest they can build solidarity, share resources, reduce stress and assist communities to lobby for better access to care and rights 16…”
Section: Introductionmentioning
confidence: 99%